Flame Behaviour in an Acoustically Forced Gas Turbine Combustor - Ruggles, Adam (Cranfield University, 2009)
A swirl stabilised dump combustor capable of imposing flow perturbations creating combustion instabilities has been designed and commissioned. The capability of supplying different fuel mixtures (methane hydrogen blends) has been incorporated. Additional capability is the facility to preheat the combustion air prior to chamber entry and to be able to introduce dilution air into the chamber. The chamber itself is of fused silica quartz to allow non-intrusive optical diagnostics. High speed CH* Chemiluminescence has been performed to qualitative characterise the unstable heat release rate of pure methane and methane hydrogen blended flames to allow analysis of the mean deconvoluted flame structure. High speed Stereoscopic Particle Imaging Velocimetry (SPIV) has been used to acquire the flow field throughout the chamber and focusing upon the Annulus entry. These diagnostics have been phase locked to the imposed perturbation. A selection of conditions is presented with three different perturbation frequencies within the low frequency range. These reveal vastly different reacting and flow field structures. The difference of structures is attributed to behaviour of the IRZ (Internal Recirculation Zone) and CRZ (Corner Recirculation Zone) in altering the flame shape. All conditions exhibited the axisymmetric/bubble vortex breakdown mechanism responsible for stabilisation. Both single cell and double cell structures were observed in the mean flow field vector maps. The mechanism of oscillating heat release rate is attributed to oscillations of flame surface area. Profiles of integrated heat release rate and flame exhibit the same profile shape and behaviour correlating very well. The inclusion of hydrogen had no quantifiable impact upon the mean reacting or flow field structures using the current diagnostics. Investigation into the nature of the turbulence of the shear layers close to the annulus is presented for three perturbation frequencies. This highlighted periodic structures within the turbulence corresponding to the imposed perturbation frequency. It was found that excitation of both shear layers for all turbulent components was not always true and depended upon the perturbation frequency and flow structure close to the annulus. Two oppositely rotating vorticity structures were revealed attached to the outer and inner circumference of the annulus. These structures protruded into the chamber and spread radially. Frequency analysis of these two structures revealed both were oscillating at the perturbation frequency indicating vorticity shedding. The mean vorticity structures are shown to be influenced also by the behaviour of the recirculation zones.